The Urgency of Role Playing Models in Improving the Character of Speech Manners at P5 Activities in Elementary Schools - Nurishlah, Laesti; Subiyono, Subiyono; Safitri, Siti Nurul (Jurnal Ilmiah Wahana Pendidikan, 2023)
The learning process often involves reflection on the experience and knowledge gained. Through this reflection, individuals can develop a deeper understanding of themselves, their values, and how they want to shape their character. This study aims to analyze the urgency of role playing models in improving the character of manners and speech in P5 activities in elementary schools. The research method used is library research with a qualitative research approach. The role playing model creates an active and enjoyable learning environment where students can be directly involved in the learning process, thereby increasing their engagement and retention of the concepts taught. Through role playing, students learn to value and respect the opinions of others, which can help strengthen interpersonal relationships and create a more positive and inclusive school environment. By considering the urgency and benefits offered by the role playing learning model, its use is expected to be an effective strategy in improving the character of manners and speech in P5 activities in elementary schools